2014
DOI: 10.1155/2014/687469
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Activation of the Excitatory Neurons Expressing CaMKIIαin the Ventral Tegmental Area Upregulates the Locomotor Activity of Free Behaving Rats

Abstract: The ventral tegmental area (VTA) plays an important role in motivation and motor activity of mammals. Previous studies have reported that electrical stimulations of the VTA's neuronal projections were able to upregulate the locomotor activity of behaving rats. However, which types of neurons in the VTA that take part in the activation remain elusive. In this paper we employed optogenetic technique to selectively activate the excitatory neurons expressing CaMKIIα in the VTA region and induced a higher locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…This body of work has led to several widely accepted principles regarding DA's various functions. These include the idea that nigrostriatal DA neurons projecting to dorsal striatum and ventrolateral putamen are principally engaged in motor control (Guo et al, 2014;Puryear et al, 2010), whereas DA neurons within the ventral tegmental area (VTA) projecting to ventral striatum are primarily involved in reward processing. Within the VTA, it has further been suggested that phasic DA is responsible for encoding reward prediction errors (RPEs) capable of driving reward-related reinforcement learning (Schultz, 2002) via receptor subtype-dependent potentiation or depression within 'go' and 'no-go' pathways in the striatum (Frank and O'Reilly, 2006;Frank et al, 2004;Reynolds et al, 2001).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This body of work has led to several widely accepted principles regarding DA's various functions. These include the idea that nigrostriatal DA neurons projecting to dorsal striatum and ventrolateral putamen are principally engaged in motor control (Guo et al, 2014;Puryear et al, 2010), whereas DA neurons within the ventral tegmental area (VTA) projecting to ventral striatum are primarily involved in reward processing. Within the VTA, it has further been suggested that phasic DA is responsible for encoding reward prediction errors (RPEs) capable of driving reward-related reinforcement learning (Schultz, 2002) via receptor subtype-dependent potentiation or depression within 'go' and 'no-go' pathways in the striatum (Frank and O'Reilly, 2006;Frank et al, 2004;Reynolds et al, 2001).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 99%
“…First, there is clear evidence from both human and primate electrophysiological studies that nigrostriatal DA neurons also exhibit many of the phasic RPE-type signals previously believed to exist primarily within the ventral striatum (Varazzani et al, 2015;Zaghloul et al, 2009), blurring the line between DA's putatively distinct roles in movement and reward. Conversely, whereas nigrostriatal DA projections are thought to primarily regulate motor function, electrophysiologic, and optogenetic studies have revealed that DAergic neurons in the VTA may also contribute to initiation of locomotor activity (Guo et al, 2014;Puryear et al, 2010), which may reflect motivational aspects of motor output. In addition, the discovery of heterogeneous populations of DA neurons within the VTA that selectively respond to either rewards or punishments and project either to ventral striatum or medial prefrontal cortex (mPFC), respectively, raises questions about the long-held view that DA neurons' primary response to negative outcomes was limited to transient 'dips' in firing (Lammel et al, 2011;Lammel et al, 2012).…”
Section: Normal and Abnormal Da Function In The Context Of Motivationmentioning
confidence: 99%
“…Another possible explanation for the discrepancy in metabolic phenotype between the CamK‐IRKO females and GABA‐specific InsR KO females is that a CamkIIα ‐Cre‐negative GABAergic population exists and plays a critical role in mediating the central effects of insulin on energy homeostasis. One such neuronal population may be tyrosine hydroxylase (TH) neurones in the ventral tegmental area (VTA) because mice exhibiting InsR deletion from VTA TH neurones exhibit an obesogenic phenotype and many of these VTA TH neurones express glutamic acid decarboxylase (GAD, an enzyme critical for GABA synthesis) but not CamkIIα . However, if this is indeed the case, insulin signalling via these putative neurones may likewise be sufficient to permit normal reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…When a 1.3 kb mouse CaMKIIα promoter was used in lentiviral vectors, transgene expression restricted to excitatory neurons was also observed (Liu et al, 2013). AAV with the CaMKIIα promoter appeared to induce transgene expression preferentially in excitatory neurons (Guo et al, 2014;Johansen et al, 2010), although expression was not restricted to excitatory neurons (Nathanson et al, 2009a;Nathanson et al, 2009b). In the cerebellar cortex, it was reported that the endogenous CaMKIIα protein was exclusively expressed in Purkinje cells (Ichikawa et al, 1992).…”
Section: 2mentioning
confidence: 99%
“…On the other hand, small fragments of specific promoters have been used for AAVs (Guo et al, 2014;Johansen et al, 2010;Kügler et al, 2003), and hence this may be one way for achieving cell-type selective expression of molecules in a given area of the brain. However, AAVs with specific promoters have not been systematically tested in the cerebellum to date.…”
mentioning
confidence: 99%